2018
DOI: 10.3389/fmars.2018.00354
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sustained Photoprotective Non-photochemical Quenching in Low Temperature and High Light Acclimation in the Bloom-Forming Arctic Diatom Thalassiosira gravida

Abstract: Thalassiosira gravida is a major Arctic diatom responsible for the under-ice spring bloom. We investigated T. gravida physiological plasticity growing it at two temperatures (0 and 5 • C) and under different light intensities typically found in its natural environment. T. gravida showed remarkable thermal-and photo-acclimatory plasticity including: low light saturation parameter for growth (K E) and photosynthesis (E K), low µ max but relatively high Chl a/C, low C/N, and decreasing light-saturated carbon fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 106 publications
2
54
1
Order By: Relevance
“…, A and C; see also Lacour et al. ). Remarkably, when normalized to E/ K E , the amounts of XC pigments were very similar in both species independent of the temperature (Figs.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…, A and C; see also Lacour et al. ). Remarkably, when normalized to E/ K E , the amounts of XC pigments were very similar in both species independent of the temperature (Figs.…”
Section: Resultsmentioning
confidence: 77%
“…, Lacour et al. , ), to normalize the growth irradiance E to K E to provide a relative scaling of the energy pressure on the photosynthetic apparatus. When analyzed against E/ K E , the amount of XC pigments was better conserved among temperate and polar microalgal species (see Table ) and conditions (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum growth rates obtained here at LL and HL correspond to 20 and 43% of this µ max , respectively, representing a relatively small growth increment given the 36-fold difference in irradiance between the two treatments and the fact that irradiance at LL was lower than the half-saturation constant for light at 0 • C (K E = 9.5 µmol photons m −2 s −1 ; Supplementary Figure 1). Recently, it has been suggested that the relatively low growth rates at 0 • C can be attributed to the limitation of C fixation resulting from the slow catalytic activity of Rubisco (Young et al, 2015;Lacour et al, 2018). In this context, the strong control of temperature on C fixation presumably nullifies the energetic advantage of using NH + 4 .…”
Section: Effect Of N Form On Growth Rates and Stoichiometry At Low Tementioning
confidence: 99%